TRUST IN SCIENTIFIC KNOWLEDGE UNDER THE CONDITIONS OF NEW TREATS FOR NATIONAL SECURITY OF RUSSIAN FEDERATION - S. A. Kravchenko; A. I. Podberezkin (Vestnik MGIMO-Universiteta, 2018)
The article shows that the validity of scientific knowledge being trustworthy is extremely important for ensuring national security. At the same time, there are objective and subjective factors that undermine confidence in it. Among the ob-jective factors is the formation of a reflexive socio-natural reality that acquires a non-linear character of development that, accordingly, implies the formation, of non-linear knowledge based on the transition from the traditional revealing of rigid correlations between facts and phenomena to a theoretical and methodo-logical instruments that can take into account many uncertainties that are manifested in the form of social disruptions, cultural traumas, unintended conse-quences of the innovation human activity. In essence, the instruments for the for-mation of non-linear knowledge is only being created, therefore, “approved, es-tablished” knowledge sometimes comes to the normative documents devoted to Russia’s security, but related to previously existing realities and other time creat-ing problems for the scientific forecast of the development of international and military-political relations. If the results of the natural sciences are absolutized and counterposed to the social and human sciences, as well as interdisciplinarity, this also makes the final knowledge vulnerable.Subjective factors significantly affect the validity of scientific knowledge. The researchers are inevitably influenced by the features of civilization and culture in which they live and work, the experience of socialization and self-socialization. But the greatest damage to the validity of knowledge is inflicted when national interests are replaced by group interests, especially personal interests of scien-tists.These complicating realities demanded a transition from unconditional trust to scientific knowledge to reflexive trust, the concept of which is proposed: this type of trust is based on risk as a certain degree of confidence in the adequacy of the involved theoretical and methodological instruments; as scientific as well as social rationality is considered; a critical test of any theory is assumed; there tak-en into account the factor of staged trust that is spreading in virtual reality; in the validity of knowledge the criterion of its humanistic component is introduced.